Dark sides of deepfake technology - Veljković, Sanela Z.; Ćurčić, Milica T.; Gavrilović, Ilija P. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Artificial intelligence can be used for both positive and negative purposes. In recent years, the use of deepfake technology has attracted significant attention. Deepfake technology replaces a person's face and creates events that never happened. While the use of deepfake was more noticeable in the past, the technology has advanced so rapidly that today it is impossible to determine if the content is fake or not. As a result, there is erosion of trust in the media and political institutions, manipulation of public discourse, as well as the spread of disinformation and fake news. The aim of this work is to examine the methods of creating deepfake content and explore the possibilities for detecting such content. A special focus is placed on investigating the dark side of deepfake technology, i.e., the negative purposes for which deepfake technology can be used.Methods: Through the use of literature review methods and content analysis, this work has provided a systematization of knowledge about deepfake technology, as well as an analysis of relevant data in this field regarding the potential misuse of deepfake technology. Deepfake technology and its use are viewed from a security perspective, i.e., how the use of these technologies can pose a social hazard. Future research should be designed to be multidisciplinary, integrating knowledge from social sciences (security, sociology, psychology) and technical sciences (information technology).Results: The results of this research show that in a positive context, the use of deepfake is associated with medicine, the film industry, entertainment, and creative endeavors. However, deepfake is often used to create pornographic content, revenge porn, fake news, and various types of fraud.Conclusion: Deepfake technology is neutral in the sense that the purpose of its use depends on the individual creating the content. The use of both artificial intelligence and deepfake technology raises complex legal and ethical questions. Although there is noticeable potential for societal improvement offered by these technologies, deepfake technology simultaneously poses a serious risk to human rights, democracy, and national security. Therefore, the misuse of deepfake technologies represents a social hazard for the entire population of any country. Women are particularly vulnerable due to the possibility of creating pornographic content and revenge porn using deepfake technology, although victims of this act can also be men.
Keywords: deepfake; pornographic content; cyber violence; scams; fake news